Need Analysis to Develop Fluid Digital Teaching Material Integrated STEM and Ethnoscience to Promote Conceptual Understanding and Creative Thinking Skills of Students - Parhannes, Al Puja; Asrizal (Journal of Innovative Physics Teaching, 2025)
Twenty first century learning requires students to master concepts and have the ability to think creatively in solving contextual problems. However, based on observations at SMA Pertiwi 1 Padang, several problems were found in physics learning, namely the limitations of digital teaching materials, problems with fluid materials, low mastery of students' concepts, creative thinking skills that have not yet developed, and teaching materials that have not been integrated with STEM and ethnoscience. To respond to this, a needs analysis stage was carried out with a Research and Development (R&D) approach using the Hannafin and Peck models. Data was collected through questionnaires to 33 students and 3 physics teachers, a discourse test to reveal problems with fluid materials and creative thinking skills, and mid-semester exam results to see the mastery of concepts. The results of the analysis show that teaching materials are not optimally supporting ICT-based learning and the integration of STEM and ethnoscience. Students' scores are still below the minimum completeness criteria. These findings show the need to develop innovative, interactive, and contextual digital teaching materials to facilitate more meaningful physics learning